‘Me and the Sky’: smashing the glass ceiling in Come from Away, neoliberal feminism, and climate change - O'Malley, E (Studies in Theatre and Performance, 2024)
This is the final version. Available on open access from Routledge via the DOI in this record This article considers neoliberal feminism and environmental concerns in Irene Sankoff and David Hein’s musical Come from Away. While the musical is not directly concerned with anthropogenic climate change, many types of sky appear as thematic and metaphorical preoccupations in the piece: feminist blue skies, stormy Newfoundland skies, the clear skies of the American Dream, skies of terror, and skies of war. I argue that Come from Away hides the tragedy of climate change in plain sight, in the sky. Undertaking a close analysis of the showstopping number ‘Me and the Sky,’ sung by the airline pilot Beverly Bass – based on the real-life woman of the same name – I observe the rift between neoliberal feminist success, acts of terror, and the slow-moving tempo of a changing climate. Come from Away’s celebration of neoliberal feminism is cut short in the song, but it foreshadows the possibilities of a more successful recognition of the conjunction between feminist and environmental awareness.